Development of a Double-Cutting Blade Sharpening Jig to Reduce Setup Time at PT XYZ - Agus Widodo; Agung Tri Tjiptadi; Merdieco Rivandi; Joko Prasetyo (INKOFAR, 2026)
Background The sharpening process of double-cutting blades plays a critical role in maintaining production efficiency in manufacturing industries. However, the existing sharpening jig requires complex setup procedures involving dial indicator adjustments, resulting in prolonged setup and machining times that limit productivity and make it difficult to achieve production targets. Purpose This study aims to develop and modify a double-cutting blade sharpening jig to simplify the setup process, reduce sharpening time, and improve productivity in the blade maintenance process at PT XYZ. Methodology The sharpening jig was designed using SolidWorks software to develop a three-dimensional (3D) model that facilitated an efficient and accurate design process. The jig was then fabricated through machining operations, including surface grinding and milling. The effectiveness of the modified jig was evaluated by comparing the sharpening performance before and after the improvement based on the total processing time required to sharpen ten double-cutting blades.. Findings The modified sharpening jig simplified the operating procedure by eliminating the need for dial indicator adjustment and repeated setup operations. Performance evaluation showed that the original jig required 6 h 49 min 58 s to sharpen 10 double-cutting blades, whereas the improved jig completed the same task in 4 h 32 min 32 s, corresponding to a processing time reduction of approximately 33.5%. In addition, the average sharpening time was reduced to 27 min 15 s per blade, demonstrating a significant improvement in operational efficiency and productivity Implications The proposed jig provides a practical solution for reducing setup complexity and machining time while improving production efficiency. The simplified design can support lean manufacturing initiatives by minimizing non-value-added setup activities, increasing equipment utilization, and reducing operational costs associated with blade maintenance. Originality This study introduces an improved double-cutting blade sharpening jig that eliminates dial indicator adjustments through a simplified fixture design. The proposed modification not only reduces setup time but also enhances machining efficiency, offering a practical and cost-effective solution for improving blade sharpening operations in manufacturing environments..